Zine Production with Queer Youth and Pre-Service Teachers in New Brunswick, Canada: Exploring Connections, Divergences, and Visual Practices - Burkholder, Casey; Hamill, Katie; Thorpe, Amelia (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
Queer, trans, and non-binary youth navigate school spaces punctuated by erasures, silences, and oppression, and resist these experiences through solidarity-building, activism, and art practice. In this article, we seek to centre experiences of school and society as important spheres of inquiry through participatory visual research with queer, trans, and non-binary young people (ages 12 to 17) and pre-service teachers and community educators (ages 22 to 40) in Fredericton, New Brunswick, Canada. Using an intersectional lens, we consider how intersecting power structures—gender, race, class, and disability—produce unequal impacts in relation to school and social experiences in New Brunswick. Centring youth agency, we position youth as knowledge producers through participatory visual methods of inquiry, including the making of zines (DIY print productions). With youth and pre-service teachers, through inquiry into existing and desired school and social experiences, we seek to make visual the practice of intergenerational solidarity building through zine production.